How Do Financial Risk and Banking Globalization Affect Renewable Energy? A Nonlinear Analysis - Alsagr, Naif; Belkhaoui, Samir; Ullah, Sana (International Journal of Energy Economics and Policy, 2025)
Renewable energy is a panacea for global issues like climate change and energy security. However, deploying renewable energy plants is costly and requires too much initial investment. Therefore, reducing financial risk and enhancing banking sector globalization can significantly enhance renewable energy consumption (REC). Previously, most empirical studies utilized the symmetric assumption; however, we have employed the asymmetric assumption to analyze the effect of financial risk and banking sector globalization on REC in this analysis. Thus, the primary research question in this analysis aims to answer is whether financial risk and banking sector globalization affect the REC symmetrically or asymmetrically, using linear and nonlinear ARDL methods. The linear model results indicate that banking globalization, GDP, and environmental policy stringency are associated with an increase in REC; however, financial risk is associated with a decrease in REC. On the other side, the nonlinear model result highlights that positive changes in banking globalization, fall in financial risk, GDP, carbon emissions, and environmental policy stringency increase the long-run REC, while the rise in financial risk and fall in banking globalization reduce the long-run REC. In the short run, banking globalization and GDP increase the REC in the linear model, while the rise in financial risk reduces the REC in the nonlinear model. Thus, by reducing financial risk and promoting banking globalization, policymakers can increase REC by providing greater financial access to businesses and individuals.